The Effect of Dual Antiplatelet Post Percutaneous Coronary Intervention On Aggregation of Platelet In Myocardial Infarction Patients With Diabetes Mellitus and Non Diabetes Mellitus - Rahmawati, Yessi Asli; Yogiarto, Mohammad; Zulkarnaen, Bambang Subakti (Indonesian Journal of Pharmacy, 2018)
To analyze the differences in the effect of dual antiplatelet post PCI on the percentage of aggregation in myocardial infarction patients with DM and non DM. Percentage of aggregation were analyzed using light transmission aggregometry (LTA) before loading dose, after PCI, and after maintenance dose of dual antiplatelet (aspirin 100mg and clopidogrel 75mg). Total 22 patients were participated in this study divided into 10 and 12 patients in diabetic and non diabetic group. Percentage of aggregation after taking dual antiplatelet maintenace dose decrease significantly in both group (p=0.006 in diabetic group and p=0.002 in non diabetic group). Mean reduction of percentage of aggregation in diabetic group (3.30Â±2.91%) is less than non diabetic group (6.83Â±5.97%). Statistical analysis shows that the mean reduction of percentage of aggregation between two groups were not significantly different (p>0.05). Mean percentage of aggregation after dual antiplatelet maintenance dose was higher in diabetic group and mean reduction of percentage of aggregation was higher in non diabetic group, although statistically in both group it is not significantly different.